Development of 3D mock-up media for respiratory system learning in elementary schools - Muna, Nailil; Zumrotun, Erna; Attalina, Syailin Nichla Choirin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
Students often struggle to understand scientific concepts due to their abstract nature and the limited use of interactive learning media. This study aims to develop 3D mock-up media for learning about the respiratory system in elementary schools. The research adopts an R&D approach using the ADDIE development model. The study participants included one teacher and 25 fifth-grade students from SDN 3 Ngeling. Data collection methods encompassed observation, interviews, questionnaires, as well as pre-test and post-test. Data were analyzed qualitatively and quantitatively to assess the feasibility of the product. The results of the validity test from the media validator obtained a score of 98.6% and 97.3% with a very valid category. In comparison, the material's validity test achieved a 97.75% result, placing it in a very valid category. This shows that this media is valid for use in research. In addition, the results of the student and teacher questionnaires also showed positive results, respectively 95% and 96% with a very good category, thus indicating that this media is feasible and effective for use in learning the respiratory system. The results of the paired sample T-test, with N-Gain values of 0.000 and 0.662, indicate differences and improvements in student learning outcomes. As a follow-up, it is expected that 3D mock-up media can be combined with digital technology to improve students' learning experiences.